Amorphous solid dispersions of sulfonamide/Soluplus® and sulfonamide/PVP prepared by ball milling - HEALY, ANNE (My University, 2013)
The aim of this paper is to investigate the physicochemical properties of binary amorphous dispersions of poorly soluble sulfonamide/polymeric excipient prepared by ball milling. The sulfonamides selected were sulfathiazole (STZ), sulfadimidine (SDM), sulfamerazine (SMZ) and sulfadiazine (SDZ). The excipients were polyvinylpyrrolidone (PVP) and polyvinyl caprolactam-polyvinyl acetate-polyethylene glycol graft co-polymer, commercially known as Soluplus®. Co-milled systems were characterised by powder X-ray diffraction and differential scanning calorimetry. PVP was shown to form amorphous dispersions over a wider composition range than Soluplus® for the four sulfonamides tested. Moreover, amorphous dispersions made with PVP were homogeneous [single glass transition (Tg)], while amorphous dispersions made from Soluplus® were heterogeneous (two Tgs). This behaviour is consistent with the fact that all the sulfonamides tested presented a lower solubility in Soluplus® than in PVP, as evidenced by Flory-Huggins parameters determined. Amorphous dispersions of SDM with Soluplus® could be produced even though SDM does not amorphise alone upon milling and Soluplus® presents Tg at a lower temperature than SDM. Amorphous dispersions of SMZ could be prepared with a lower excipient concentration compared to STZ, SDM and SDZ, which may reflect the one-dimensional H-bonding network in SMZ compared to the 2D or 3D H-bonding network found in the other sulfonamides. Stability tests (60% RH/25°C) revealed that dispersions made with Soluplus® remained dry and powdery compared to those made with PVP that formed a sticky paste in less than 2 weeks, indicating a possible advantage of using Soluplus® in terms of increased physical stability under high humidity storage conditions.
PUBLISHED
Keywords: milling and Soluplus®; milling and Soluplus®